Evaluation and analysis of the computation cost of linear network coding - PU Bao-xing1; WANG Wei-ping2 (Tongxin xuebao)
The complexity of algebraic operation methods on Galois fields was analyzed and the operation mechanism of linear network coding was anatomized.Based on deterministic network coding data transmission and random network coding data transmission for single-source multicast connection,the mathematic model had been created to estimate the computation cost of linear network coding and the relationship between operation cost and environmental parameters had been revealed.The key factors of affecting the operation cost were also analyzed.The analysis results indicate that computation cost can be decreased through properly choosing environment parameters.Numerical calculation and simulation results demonstrate the correctness of the proposed model and validate the theoretical analysis.